DAMPAK PEMBANGUNAN JEMBATAN SURAMADU TERHADAP PEREKONOMIAN PULAU MADURA (Studi Kasus Kabupaten Bangkalan) - Mohammad Effendi; R. Mulyo Hendarto (Diponegoro Journal of Economics, 2014)
ABSTRACT Infrastructure development has a very vital role in the fulfillment of people's basic rights. It has very strong linkages with social welfare and environmental quality, also on the economic growth process of a region. The suramadu bridge project development has a very strategic role in the island ofmadura, which will boost economic activity, distribution of goods and services as well as tourism activities. Madura island which became part of the province of east java has a less favorable conditions before. The matter was slow economic growth and lags income per capita.This research aimed to describe and to analyze the economically impact of Suramadu bridge project develompent to madura island with a case study in Bangkalan. This research used a qualitative research with desciptive approach. This study’s main focus is to analyze the impact of Suramadu bridge project development to the economy development of Bangkalan region and how the developmental policy impacted suramadu`s developmental area.The bridge`s project development has a multiplier effect to people in Madura for saving their times and cash on bussiness travel to Java. On the other hand, it caused population growth in suramadu area, it shows by an increasing number of people, so the demand for residential home was also increase. In addition, to fit the increased demand for residential houses is to develop the shopping centers and other supporting infrastructures. Suramadu development policy is an attempt to improve the infrasctructures to meet the complex needs. Generally it has whether positive or negative impacts. The government`s intervention on this project development was to establish an agency of Suramadu area development(BPWS).